Sim-boost: an alternative technique for measuring labour productivity at construction sites - Hanafi, Mohd Hanizun (2008)

(untitled)
Previous studies showed that labour productivity level has continuously been low at construction sites. One of the appropriate approaches for improving the labour productivity is by implementing the industrialised building system. However, this approach is fewer implemented globally in the construction sites because the previous researchers concentrated more on the IBS hardware rather than IBS software. Earlier productivity measuring techniques based on statistical theory, expert system and neural networks models are said to be unsatisfactory because they are incapable of considering the combined effects of the various factors and cost in measuring labour productivity at work sites. Therefore, this research has focused on developing an alternative labour productivity measurement technique to be better able to overcome the shortcomings in the others called SIMBOOST. A series of experiments via simulation model have been performed, which depicted detailed information on the labour productivity in the construction sites. Evidently, the comprehensive information namely labour productivity of monetary units, labour productivity ratio and loss of labour productivity in terms of percentage and monetary unit of the installation of Industrialised Building System (IBS) components in the construction sites have been fully generated via this approach.